Analisis Daya Saing Ekspor Komoditi Kepiting Provinsi Bali - Ogi Suparsa, I Putu; Martini Dewi, Ni Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 6, Juni 2016 (pp. 652-728), 2016)
Commodity crabs h as demand is which are increasing in every year from many countries, it is for consumption in the restaurant and hotel. This purposeof this study is to find out how the  competitiveness and influence of simultaneously and partially on the US dollar exchange rate, inflation, and the price of crab to the export value of commodities crab Province Bali in 2000-2013. In this study using techniques index analysis revealed comparative advantage ( RCA ) and multiple linear regression using time series data from the years 2000-2013. Based on the calculation of the index revealed comparative advantage (RCA) RCA showed <1, this means that commodity crab Bali province has not had that competitiveness and can not be the leading sectors in the export of Bali Province. Meanwhile based on linear regression, test results can be known simultaneously US dollar exchange rate, inflation, and the price of crab significant effect. In the partial test results claimed the dollar exchange rate and a significant and positive effect, also the most dominant variable.
Keywords: competitiveness; exports of crab; the dollar exchange rate; inflation; price